Takotsubo cardiomyopathy -— a case report - Khan, Ali Nawaz; Malik, Erum Shahzadi; admin (Journal of the Pakistan Medical Association, 2023)
Takotsubo Cardiomyopathy is a cardiac syndrome of rare type involving apical akinesis of the left ventricle. Symptoms of acute myocardial infarction, i.e. chest pain, S-T changes, and positive cardiac enzymes, are observed in patients with Takotsubo Cardiomyopathy. Cardiac angiography of Takotsubo Cardiomyopathy patients manifest left ventricular apical ballooning with no remarkable coronary artery stenosis. Mostly the cases are managed on the lines of treatment for Acute Coronary Syndrome. We present a case of Takotsubo Cardiomyopathy in a teenage girl from Karachi, Pakistan. The prevalence of Takotsubo Cardiomyopathy in Pakistan is yet to be mapped due to its rarity. Key Words: Takotsubo Cardiomyopathy, Rare Cardiac Syndrome, Teenage Girl, Karachi, Pakistan.